Pengaruh Pendidikan Kesehatan Metode Peer Group Tentang Menstruasi Terhadap Kesiapan Menghadapi Menarche Pada Siswi SD Kelas V Di SD Pundenarum I Kecamatan Karangawen Kabupaten Demak - Nurul Fatimah; Isy Royhanaty; Sawitry Sawitry (Poltekkes Kemenkes Surakarta, 2017)
Abstract: Menstrual Health Education Peer Group Method, Readiness To Face Menarche. Menarche in young women could cause anxiety, caused by mental preparedness, lack of knowledge and attitude were quite good physical and psychological changes. Results interview 10 students 8 students say anxiety and fear, while 2 students can answer understanding of menstruation. They had never received information about menarche and special place to ask about reproductive health. To determine the influence of menstrual health education through peer group method to the v grade students of pundenarum i elementary school, karangawen, demak. This was a pre-experimental study, with One Group Pre Test Post Test Design and Total sampling technique. The population was 35 V grader students in elementary Pundenarum I. Wilcoxon statistical test. There was a difference before and after the peer group health education about menstruation which seen from the median pretest was 18 and posttest was 28. Statistical test results obtained P-Value = 0.000. There was the influence of menstrual health education through peer group method to the v grade students of pundenarum i elementary school, karangawen, demak. Can disseminate to the elementary school using the Peer Group increase preparedness in the face of menarche.